Issues in Science and Technology Librarianship at 15…at 20: A Reflection. - Andrea L. Duda (Issues in Science and Technology Librarianship)
The author reflects on the 15th and 20th anniversaries of "Issues in Science and Technology Librarianship" (ISTL). The first issue of ISTL was released in December 1991 by Harry Llull of the University of Mexico. Considered one of ISTL's best moves was adding the refereed articles section to the journal, which provided a place for people to publish the article they needed for promotion and tenure.